A [in]efetividade dos direitos nos contratos de planos privados de acesso à saúde a partir da concepção kantiana de responsabilidade - Veloni, Raphael Bruno (2020)
In this work, the category of the right of access to health in the private sphere is exposed, which is qualified by the risk of [in] effectiveness of its rights and by the proliferation of attacks on the person. In the public and private spheres, the right of access to health suffers undue refusals, by the State or Health Plan Operators, causing recourse to the judiciary. Thus, the judicialization of health and the contained litigation have been studied in order to be adequate to the scarcity of resources in the realization of such right, diversity of risks to the person and proliferation of contractual breaches, demonstrating the need to rethink the scope of the effects of civil responsibility. In this Dissertation, the objective is to study the dialogue between negative and positive sanctions in the measurement of moral damages in cases of liability of Health Plan Operators. The general objective is to analyze the content of the repressive and promotional functions, with respect to the sanctions extracted from art. 944, sole paragraph, of CC / 02. The problem that guided this research was: How can promotion and repression, applied through civil responsibility for off-balance sheet damages, be a usuful means of stimulating the effectiveness of rights in the national market for private health plans? The fundamental hypothesis is that promotion and repression, based on the application of the Kantian conception of responsibility, can intensify the scope of the effects of civil liability for off-balance sheet damages, stimulating the fulfillment of rights and discouraging their intentional violation in the national market. In this way, the research is based on the work of Immanuel Kant, notably in his conception of responsibility. The Kantian judicial imputation is adopted as a method, which makes it possible to intensify the scope of the effects of civil liability by combining positive retributions, compensations and negative retributions with merit, debt and demerit, respectively. To this end, a qualitative analysis was carried out based on data on the extent of the effects of the Operators’ civil liability, as well as those on the Kantian conception of responsibility. These data pertinent to the theme of this research were taken from the Brazilian and foreign legal literature, from the jurisprudence of the Superior Court of Justice (STJ) and from other normative sources, especially those related to responsibility and social control measures in the Civil Code, in the Code of Consumer Defense and Protection and in the Law on Private Health Care Plans and Insurance. In the research, evidence was found of the utility, in the scope of civil responsibility, of the use of various positive and negative social control measures. Such construction is of superior security and functionality if instructed by the democratic debate at the expense of the interpretation of general clauses. This democratic construction would have the ability to instruct a beneficial system to meritorious economic agents, as well as to elaborate disincentives to the repeated violation of the right of access to health through positive and negative rewards, but without abdicating advances in civil dogmatics on damage repair. In this way, the Kantian conception of responsibility would broaden the definition of civil responsibility by offering a starting point for these democratic constructions.